BIOLOGY OF BRACHYDANIO RERIO (HAMILTON, 1822) FROM NORTH EASTERN HILL REGION, INDIA - MAHAPATRA, B K; LAKRA, W S (Journal of the Inland Fisheries Society of India, 2021)
The Zebra danio, Brachydanio rerio (Hamilton) is one of the most popular Indian ornamental fish both locally and globally. Length-weight relationship of B. rerio indicating negative allometric growth in male, positive allometric growth in female, isometric growth in combined sex and found to be significantly different at 1% level. The fish does not follow the cube law strictly. Maximum number of fishes were found distributed in 26 to 30 mm size group (33.52%) followed by 21 to 25 mm size group (23.98%). In natural condition the fish feed predominantly on phytoplankton (98 %) the rest was zooplankton (2%). Bacillariophyceae was the most abundant group with an average of 50%. Minimum number of ova produced was 215 (29 mm; 0.20 g) and maximum ova was 2836 (49 mm; 1.81 g). Sex ratio in nature was 1female:1.77male. 5+ months old of males and 6+ months old of females were attained the first maturity. Successfulnspawning was recorded in captive condition. 288-300eggs are found per spawning per female. The Gonado-Somatic Index for the gravid females during breeding period ranged 8.06 - 28.95 with an average 16.14. The fertilized eggs measuring 0.8-1.3 mm in diameter were demersal, non adhesive, almost spherical in shape, optically transparent and unpigmented. The embryos hatched within 40-42 hrs and measured 2.8Â±0.1 mm in total length. Key words: NEH region, Brachydanio rerio, biological characters, breeding, development biology